Ultrasound of the infant hip: manual fixation is equivalent to Graf's technique regarding image quality-a randomized trial - Peter Voitl; Christian Sebelefsky; Sara Hosner; Astrid Woditschka; Susanne Diesner; Andreas Böck (BMC, 2019)
Abstract Background In Middle Europe ultrasonography is the standard method used to screen for developmental dysplasia of the hip in infants. Our aim was to determine whether manual fixation of the child is equivalent to Graf's technique regarding image quality. Methods This randomized trial was conducted at a free-standing general pediatric outpatient clinic in Vienna, Austria. Healthy infants in the 1st and between the 6th and 8th week of life with no hip malalignment were included. After randomization, Group 1 was examined using Graf's fixation device and participants in Group 2 were fixated on the examination couch by their parents. In a second step, all images underwent a blinded evaluation. Results A total of 117 babies (Group 1: n = 62, Group 2: n = 54, excluded: n = 1) were examined and 230 images (Group 1: n = 122, Group 2: n = 108) were evaluated, of which 225 were sonographically normal. Two images, showing a type IIa right hip and a type IIa + left hip respectively, were excluded. One participant had to be excluded as the respective images showed two pathologic hip joints. Two images in Group 1 and three in Group 2 were not evaluable. No statistical association between image quality (11 quality criteria and overall evaluability) and fixation technique (0.12 ≤ p ≤ 1.0 or constant) was found. Conclusions Considering sonographically normal hip joints, we found no evidence that manual fixation differed from Graf's technique regarding image quality. In future studies, hip pathologies should be included and discomfort of infants and parents during the examination should be addressed. Trial registration German Clinical Trials Register, ID: DRKS00015694), registered retrospectively on October 7th, 2018.